“See What We See”: Law Enforcement Perceptions on Using Cameras for Evidence Collection in Domestic Violence Cases - Backes, Bethany L. (Victims & offenders, 2023)
As law enforcement agencies increasingly equip officers with cameras to capture evidence, there is growing interest to explore how video evidence, and specifically video-recorded victim statements, impact domestic violence investigation and prosecution practices. This study sought to better understand how the use of cameras by law enforcement impacted evidence in domestic violence cases. Data were collected from 44 law enforcement officers across five counties as part of an evaluation examining the implementation and subsequent case outcomes of a state-led initiative to collect video-recorded victim statements in domestic violence cases. Findings suggest video statements are a positive mechanism for improving the comprehensiveness of victim statements and enhancing evidence for use in prosecution. Implications and future research directions are discussed.